Two-dimensional transition metal diseleniums for energy storage application: a review of recent developments. Issue 3 (5th January 2017) - Gao, Yong-Ping; Wu, Xu; Huang, Ke-Jing; Xing, Ling-Li; Zhang, Ying-Ying; Liu, Lu
Abstract : In this review, we have briefly summarized the applications of two-dimensional transition metal diseleniums in supercapacitors, lithium ion batteries, sodium ion batteries and hydrogen storage. Abstract : Two-dimensional transition metal diseleniums (2D-TMDSs) have recently triggered worldwide research interest due to their outstanding properties, such as abundance, low cost, chemical and thermal stability, low framework density and ease of processability. More fascinating is the fact that these materials are extensively used in energy storage (including supercapacitors, lithium ion batteries (LIBs), and sodium ion batteries (SIBs)) and hydrogen storage, and exciting progress has been recently achieved in the synthesis, characterization, device fabrication and functionalization of these 2D-TMDS materials. In this work, the properties of 2D-TMDSs and their use in energy storage are reviewed. In addition, being semiconductors with considerable mobility, TMDSs have been touted as a candidate in next generation electronics, and this review demonstrates the merits of TMDSs by intensive investigations into their use in energy storage. As a result of numerous opportunities for applications and multiple challenges to overcome, this review will be instructive and useful to researchers working in the area of 2D materials as well as scientists and engineers interested in their applications in supercapacitors, LIBs, SIBs and hydrogen storage.